2000
DOI: 10.1093/emboj/19.7.1731
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymerase mu (Pol micro), homologous to TdT, could act as a DNA mutator in eukaryotic cells

Abstract: A novel DNA polymerase has been identified in human cells. Human DNA polymerase mu (Pol mu), consisting of 494 amino acids, has 41% identity to terminal deoxynucleotidyltransferase (TdT). Human Pol mu, overproduced in Escherichia coli in a soluble form and purified to homogeneity, displays intrinsic terminal deoxynucleotidyltransferase activity and a strong preference for activating Mn(2+) ions. Interestingly, unlike TdT, the catalytic efficiency of polymerization carried out by Pol mu was enhanced by the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
300
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(316 citation statements)
references
References 61 publications
(77 reference statements)
15
300
1
Order By: Relevance
“…In the yeast Saccharomyces cerevisiae, the Pol4 enzyme, which belongs to the PolX family, has been shown to be involved in fill-in DNA synthesis during NHEJ 14 . Among PolX polymerases, Polλ is closer to yeast Pol4 while Polµ and TdT, which are highly homologous to each other, are more distantly related [15][16][17] .…”
Section: V(d)j Recombination and Dna Polymerasesmentioning
confidence: 99%
“…In the yeast Saccharomyces cerevisiae, the Pol4 enzyme, which belongs to the PolX family, has been shown to be involved in fill-in DNA synthesis during NHEJ 14 . Among PolX polymerases, Polλ is closer to yeast Pol4 while Polµ and TdT, which are highly homologous to each other, are more distantly related [15][16][17] .…”
Section: V(d)j Recombination and Dna Polymerasesmentioning
confidence: 99%
“…In contrast, the group of Honjo identi¢ed an activity acting probably upstream in the centroblast di¡erentiation pathway (see Muramatsu et al 2000). A second argument is the remarkable in¢delity of Pol m reported by the group of Blanco (Dominguez et al 2000), even though several translesion DNA polymerases (eta and iota, in particular) appear competitive in this respect (Matsuda et al 2000;Tissier et al 2000). Finally, mainly its relatedness with TdT is the most appealing feature for the immunologistö two enzymes would have evolved in higher eukaryotes: TdT, to generate diversity of CDR3 by random nucleotide insertion at the V^D^J junction; and a TdT-like polymerase with a poor ¢delity to diversify the whole V gene at later di¡erentiation steps.…”
Section: The Mutase: An Error-prone Polymerase?mentioning
confidence: 99%
“…We report here the identi¢cation of two new b-like enzymes, one of which (Pol m), isolated in parallel by the group of Luis Blanco (Dominguez et al 2000), has a preferred lymphoid expression pattern and is closely related to terminal deoxynucleotidyl transferase (TdT), an enzyme whose unique function is the diversi¢cation of the T-and B-cell repertoire.…”
Section: Introductionmentioning
confidence: 99%
“…Pol l was identified as a 55-kDa protein with high homology (identity, 41%) to TdT [Dominguez et al, 2000]. Pol l can extend unpaired primer termini by template-independent addition [Dominguez et al, 2000] though this activity is much lower than observed with TdT.…”
Section: Pol Lmentioning
confidence: 99%
“…Pol l can extend unpaired primer termini by template-independent addition [Dominguez et al, 2000] though this activity is much lower than observed with TdT. Unlike TdT, Pol l is most active when it can add nucleotides complementary to a template, and when it can recognize the 5 0 -phosphate terminus of a downstream strand associated with this template [Dominguez et al, 2000]. Together with Pol l's ability to form a complex with the NHEJ core factors Ku and XRCC4-ligase IV and take advantage of their end aligning activity, Pol l can promote NHEJ of noncomplementary ends (Fig.…”
Section: Pol Lmentioning
confidence: 99%